Impact of COVID-19 on Periodontitis and Peri-Implantitis: A Narrative Review - Mancini, Leonardo; Americo, Lorenzo Maria; Pizzolante, Tommaso; Donati, Raffaele; Marchetti, Enrico (Frontiers in Oral Health, 2022)
COVID-19 is reported as one of the most widespread diseases in the world. An extraordinary number of articles and manuscripts have focused on the inflammatory cascade and sequelae, showing the important roles of cytokines and renin-angiotensin levels and possible links to other pathologies. Nowadays, interest regarding the possible correlation between COVID-19 and periodontal and peri-implant diseases is increasing. This mini-review aims to collect data regarding the possible correlation between COVID-19 and periodontitis or peri-implantitis through the analysis of articles published in the last three years. The following keywords were used: ([periodontitis OR periodontal disease] AND [COVID-19]); ([peri-implantitis OR mucositis] AND [COVID-19 OR Sars-CoV-2]). The inclusion criteria were studies on COVID-19 or SARS-CoV-2 and periodontitis or peri-implantitis, and studies on the molecular and cellular aspect of COVID-19 in periodontal or peri-implant tissues. The search revealed 484 articles in total (PubMed 208 and Scopus 276). After a screening of titles and abstracts, 47 articles were included in the full-text analysis. Two articles comprised the peri-implant group: a short communication and a review. Regarding the periodontal group, 45 articles were selected and analyzed according to the type of study, population, and aim. Of these, 10 articles were clinical studies, and the other 35 were hypotheses, reviews, letters to the editor, or commentaries. In conclusion, according to the data extracted, a mutual correlation between COVID-19 and periodontitis can be stated; however, data linked to peri-implantitis are still missing, and future clinical studies are still needed.